Prevalence of Itch in German Schoolchildren: A Population-based Study - Grigorios Theodosiou; Theresa Nissen; Elke Weisshaar; Sandra Plachta-Danielzik; Matthias Augustin; Sonja Ständer; Laura B. von Kobyletzki; Regina Fölster-Holst (Medical Journals Sweden, 2022)
Itch is a common symptom, but there is limited evidence on the prevalence of itch in children. The aim of this study was to assess the prevalence of itch in schoolchildren. A questionnaire was developed by experts in the field and based on a literature search. The questionnaire was applied in a pilot study of 25 consecutively selected paediatric patients and their parents. It confirmed the high content validity of the questionnaire, and the questionnaire was comparable to hospital records regarding chronic itch (n = 19, mean consistency 89.47%). The questionnaire was distributed among German schoolchildren in 9/12 randomly selected primary schools in Kiel, Germany. Of 1,722 invited students, 443 schoolchildren aged 6-10 years participated, and 26.2% (n = 116) reported itch. The prevalence of acute itch was 20.0% (n = 87), and 14.7% (n = 65) reported chronic itch. Reduced sleep and mood were often related to chronic itch. This study demonstrated that itch is a common symptom in German schoolchildren.